PENGARUH GENDER & EDUCATIONAL DIVERSITY PADA JAJARAN DIREKSI DAN KOMISARIS TERHADAP INTERNASIONALISASI(STUDY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2018) - Sevliani, Merystika; Adrianto, Fajri (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract :This study aims to examine the effect of the characteristics of the board of directors and the board of commissioners on internationalization in manufacturing companies in Indonesia in 2015-2018. The independent variables in this study were the gender diversity of the board of directors, the economic background of the board of commissioners and the size of the board of commissioners, while the dependent variable used was company internationalization. This study uses 276 samples from 69 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. This research was conducted with quantitative methods using secondary data. Data analysis uses panel data based multiple regression models, and uses firm size, leverage and profitability of control variables. The results of this study indicate that the presence of women in the board of directors has no significant effect on internationalization, the economic background of the board of commissioners has a negative and significant effect on internationalization and the size of the board of commissioners has a significant effect on internationalization. Keywords: Internasionalisasi, Gender Diversity, Educational diversity, Board of Commissioners' size Abstrak: Penelitian ini